2018
DOI: 10.1002/bit.26521
|View full text |Cite
|
Sign up to set email alerts
|

Engineering tunable biosensors for monitoring putrescine in Escherichia coli

Abstract: Biosensors can be a powerful tool for real-time monitoring of specific small molecules and for precise control of gene expression in biological systems. Thus, biosensors have attracted much attention for monitoring increasing number of molecules. However, strategies to tune the properties of biosensors remain less explored, which might restrict their wide applicability. Here we report the development of tunable biosensors for monitoring putrescine, an important member of biological polyamines, in Escherichia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 53 publications
2
50
1
Order By: Relevance
“…The results were similar to that reported in a previous study. 49 This may be attributed to the fact that the biosensor detects the intracellular rather than the extracellular L-valine concentration. Although this method is not particularly precise, it confirmed that the biosensor is functional.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The results were similar to that reported in a previous study. 49 This may be attributed to the fact that the biosensor detects the intracellular rather than the extracellular L-valine concentration. Although this method is not particularly precise, it confirmed that the biosensor is functional.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…However, recent efforts have been made to sense natural products secreted into the extracellular environment as well. 137,146,[160][161][162] An elegant biosensor set-up was realised by Mukherjee et al who coupled a medium-chain fatty acid (MCFA)-responsive G protein to a receptor on the cellular membrane, enabling the transduction of subsequent signals in the presence of extracellular MCFAs. 147 Similarly, the group of Peralta-Yahya engineered a human serotonin G proteincoupled receptor to detect serotonin secreted by a serotonin producing yeast strain.…”
Section: Biosensorsmentioning
confidence: 99%
“…Naturally occurring transcription factors have become a popular option in synthetic biology, used for a variety of metabolite detection systems [ 33 ] including para-hydroxybenzoic acid [ 34 ], NADP/NADPH [ 35 , 36 ] muconic acid [ 37 ], fatty acids [ 38 ], L-lysine, 3-hydroxypropionate [ 39 , 40 ], L-valine [ 41 ], malony-CoA [ 42 ], macrolides such as erythromycin [ 43 ], and putrescine [ 44 ].…”
Section: Transcription Factor-based Biosensorsmentioning
confidence: 99%